Strategi Guru dalam Mengenalkan Literasi Awal pada Anak Usia Dini - Fauziyah Hanum, Labibah Adilah; Diana, Diana (Universitas Hamzanwadi, 2026)
The study has been conducted in the student development planning agency, as well as in the interest of implementing the initial literacy of the aisfal 54 semarang development system, focusing on both the application of the methods and the role of the existing educators in the aisfal, as well as in introducing the initial literacy to students. Data generated in the research is obtained through mechanical observation methods and structured interviews. As for the results of findings obtained in this study which include: (1) the use of learning methods such as, picture stories, journal, words, and game accretions, in promoting differentiated learning (2) teachers play as creators, facilitators, dynamitators, motivators, and evaluators in creating interactive and fun learning environments, invigorating students, and providing learning designs that meet students' needs. This finding affirms that in dealing with the challenge of students' learning ability, the teacher requires proper planning from the teacher in adapting the learning plan to the student's learning ability.